2017
DOI: 10.1161/strokeaha.116.014456
|View full text |Cite|
|
Sign up to set email alerts
|

Early Trajectory of Stroke Severity Predicts Long-Term Functional Outcomes in Ischemic Stroke Subjects

Abstract: Background and Purpose— The trajectory of neurological improvement after stroke treatment is clinically likely to be an important prognostic signal. We compared the accuracy of early longitudinal National Institutes of Health Stroke Scale (NIHSS) measurement versus other early markers of stroke severity post treatment in predicting subjects’ 90-day stroke outcome. Methods— Data are from the Endovascular treatment for Small Core and Anterior circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…A study on follow-up of 154 patients revealed an initial NIHSS < 5 and an improvement in neurological symptoms in the first 2 h after stroke to have predictive value for GFO ( 6 ). In patients with large vessel occlusion included in the ESCAPE trial and endovascularly treated, improvement in NIHSS within 48 h was a better predictor of outcome than baseline NIHSS ( 21 ). The predictive value of change in NIHSS in the early time-interval after stroke might be a reflection of reperfusion (spontaneously or by an intervention), but this could not be analyzed in this cohort since we did not collect data on reperfusion status.…”
Section: Discussionmentioning
confidence: 99%
“…A study on follow-up of 154 patients revealed an initial NIHSS < 5 and an improvement in neurological symptoms in the first 2 h after stroke to have predictive value for GFO ( 6 ). In patients with large vessel occlusion included in the ESCAPE trial and endovascularly treated, improvement in NIHSS within 48 h was a better predictor of outcome than baseline NIHSS ( 21 ). The predictive value of change in NIHSS in the early time-interval after stroke might be a reflection of reperfusion (spontaneously or by an intervention), but this could not be analyzed in this cohort since we did not collect data on reperfusion status.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results from the ESCAPE investigators showed that a neurological improvement in the first 2 days following a stroke predicted functional outcome with greater accuracy than other common variables [35]. Also, follow-up imaging was demonstrated to be a good predictor and possibly superior to mTICI scores [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Early improvement in NIHSS score may function as a surrogate marker of outcome in situations in which an mRS score cannot be obtained. 126,127 Although it is ideal to assess the patient in person, this may not always be possible, and telephone assessment of mRS score is a reasonable alternative that is well validated. 128 We understand that some patients may be lost to follow-up by 90 days.…”
Section: Clinical Outcomesmentioning
confidence: 99%